Kedudukan Korban Penyalahgunaan Narkotika dalam Hukum Pidana Indonesia dan Hukum Pidana Islam - Vivi Ariyanti (Al-Manahij: Jurnal Kajian Hukum Islam, 2017)
The term of drug abuse victims in the Act No. 35 of 2009 on Narcotics refers to a person who inadvertently uses narcotics, for being persuaded, tricked, deceived, coerced, and/or threatened to use narcotics. However, both addicts and the individual self-use drug abusers are in factvictims of syndicates of illicit narcotics trafficking. In addition, the spirit contained in the Narcotics Act also implies that narcotics addicts and abusers are victims of criminal acts of others in the form of illegal drug trafficking.Therefore, the Narcotics Act stipulates the obligation to undergo medical rehabilitation and social rehabilitation for addicts and self-use of drug abusers.On the contrary, Islamic law does not distinguish the term addicts, narcotics abusers, or victims of narcotics abuse. Islamic law tends to equate all these categories as perpetrators of narcotics abusers except those who are truely forced by others. In Islamic law, the punishment for them according to some scholars is the sanction of h}udu>d which is equated with the khamr (alcohol) drinkers, that is whipped as much as eighty times. While the opinion of other ulema, the penalty is ta’zir, of which form submitted to the ruler/government/judge. Thus, this type of ta’zir sanction in Islamic law is more in line with the prevailing laws and regulations in Indonesia.